New Evolutionary Model on "Autistic Spectrum Disorder" (PEMA), the severity scale (PASS), and the clinical questionnaire for the late teenage years and adults (PTAS-Qa) - Giulio Perrotta (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2022)
Starting from the concept of "Autism Spectrum Disorder", as framed in the DSM-V, the present research proposes a new etiological theory (PETA) focused on the evolutionary model of the neurobiological matrix, overcoming the modest or inconsistent psychodynamic or conspiracy theses present in the international scene. Based on this assumption, therefore, a new study model (PEMA) was suggested that can focus on the presence or absence of 9 dysfunctional traits (type-deficit and type-clinical features) centered on the areas of social, emotional, and cognitive-communication and interaction, grading the impairment according to a precise 5-level severity scale (PASS), underpinning the 40-item questionnaire (Perrotta Dysfunctional Traits of the Autistic Spectrum Questionnaire for the late teenage years and Adults, PTAS-Qa) on a binary Y/N scale and based on a total score of 11/11, thus offering a more structured view of the patient's cognitive and psychological organization, avoiding diagnostic fragmentations that might be inconsistent with the nosographic picture and therefore not perfectly framed. By exemplifying the category, it is, therefore, possible to more easily frame the patient, who would thus be analyzed from a strictly functional point of view, also facilitating the therapeutic interventions to be prepared, according to models already known in the literature (e.g. ABA).